Efektivitas Pemberian Aromaterapi Lavender (Lavandula Angustifolia) untuk Mengurangi Nyeri Persalinan: Tinjauan Literatur Sistematis - Amanda Rapibta Yakoeb; Fitriana; Eka Vicky Yulivantina; Evy Ernawati (LPPM STIKES Guna Bangsa, 2022)
During labor, the mother experiences pain due to contractions of the uterine muscles. These contractions are a sign to give birth to the baby and open the baby's birth canal. These contractions can cause pain experienced by many women, and most women who cannot accept the pain are caused by thoughts that are influenced by stress called fear, tension, pain (fear, tension, and pain). In addition, parity can also affect pain. Because in primiparous mothers, the pain will be more pronounced at the beginning of labor, while for nulliparous mothers the pain will be felt when the fetal head descends which will take place quickly during the second stage. The perception of increasingly intense pain can increase maternal anxiety and tension so that it is not uncommon for mothers to ask for an accelerated delivery process, namely by sectio caesar. This study uses a systematic literature review method, this method is used to identify, review, evaluate and interpret all studies that are by the criteria studied. This study also aims to examine various studies on the relationship between complementary therapy in reducing labor pain. This study uses aromatherapy where aromatherapy is a non-pharmacological technique that can increase maternal comfort during the birth process and has an effective coping effect on the delivery experience. Lavender flower is aromatherapy which contains linaly acetan and linalool as the main ingredients. The fragrant aroma produced by lavender can stimulate the thalamus to secrete enkephalin, which functions as a pain reliever and anxiety during labor.